1992
DOI: 10.1136/oem.49.5.316
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in retired coke oven plant workers.

Abstract: Lung function was studied in 354 coke oven plant workers in the Lorraine collieries (Houilleres du Bassin de Lorraine, France) who retired between 1963 and 1982 The aim of this work was to study the long term effect of occupational exposure on lung function in retired coke oven workers from the HBL. This work is part of a study on mortality and morbidity in survivors.'7 It continues a previous study carried out in 1983 on mortality which showed an excess of mortality from lung cancer (standardised mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…1 2 While lung function of coke oven workers has been investigated in several cross-sectional studies, [2][3][4][5] we have found no reported longitudinal studies. A health surveillance system for coke oven workers started in an Australian steelworks in October 1978 and was modified in July 1990.…”
mentioning
confidence: 79%
“…1 2 While lung function of coke oven workers has been investigated in several cross-sectional studies, [2][3][4][5] we have found no reported longitudinal studies. A health surveillance system for coke oven workers started in an Australian steelworks in October 1978 and was modified in July 1990.…”
mentioning
confidence: 79%
“…Selection out of a workforce because of respiratory complaints, found in several groups working in dusty environments, will tend to weaken any relationship between BHR and occupational exposure (duration at work). CHAU et al [28] did not find any adverse effect of occupational exposure on ventilatory function in retired coke-oven plant workers from Lorraine. The functional values were however mostly lower than predicted values and the most reduced index was the mean expiratory flow from 25-75% of FVC.…”
Section: Discussionmentioning
confidence: 99%
“…12 13 Chau et al investigated 354 retired male coke oven workers. 11 They found no effect of exposure to coke oven emissions on FVC, nor on other lung function indices (FEV 1 , FEV 1 /FVC, and FEF 25-75% ). They attributed the lack of association to bias of participants, healthy worker effect, and the exclusion of deceased subjects.…”
Section: Discussionmentioning
confidence: 90%
“…[5][6][7][8][9] Fewer studies have concentrated on lung function of coke oven workers. [10][11][12][13] Some investigations have reported lower lung function and higher prevalence of bronchitis. 10 12 13 A lung function surveillance system has operated from 18 October 1978 at the recovery coke ovens of a steelworks.…”
mentioning
confidence: 99%